Academic Technologies for College Students With Intellectual Disability. Issue 2 (March 2021) - Barbetta, Patricia M.; Bennett, Kyle D.; Monem, Ruba
Institutes of higher education have encountered an increase in enrollment of students with intellectual disability (ID). This increase is due, in part, to societal movements (e.g., inclusive participation in life activities) and federal legislation. There are potential benefits to both individuals with ID and society when students within this population complete college (e.g., earn certificates, a collection of completed courses and experiences, increased future employment opportunities). Nevertheless, there are barriers to college that students with ID need to overcome to have successful experiences, particularly in their academic or functional academic courses. This paper presents numerous instructional technologies grounded in behavior analytic strategies and Universal Design for Learning (UDL) that university faculty might implement in their courses and/or recommend to their students for studying to facilitate the learning of college students with ID and their classmates.